International Public Administration Reform : Implications for the Russian Federation - Manning, Nick (Washington, DC: World Bank, 2013)
This paper has four objectives: 1. To offer an analysis of public administration reform experiences in a set of countries chosen to illustrate the range and depth of recent administrative change. 2. To pick out from this analysis those variables that seem particularly relevant to the current condition in the Russian Federation. 3. To suggest a way of organizing thinking about a very complex and contested field. 4. To provide some pointers toward a reform strategy for policymakers in this area in the Russian Federation. Identifying the key country comparators and the relevant variables and offering a way of thinking about their significance are particularly important for the Russian Federation authorities as they prepare for implementation of the Program for the Reform of the Civil Service System in the Russian Federation. As reforms intensify, there will be a flood of serious, experienced international advisers and management experts, but there will also be those with "snake oil" to sell. Reformers need some lenses through which they can critically examine reform proposals and evaluate advice from experts. The paper draws its conclusions from an analysis of 14 countries selected by representatives of the Russian Federation government: Australia, Brazil, Canada, Chile, China, Finland, Germany, Hungary, the Netherlands, New Zealand, Poland, the Republic of Korea, the United Kingdom, and the United States. The World Bank was asked to look at a number of countries that faced similar challenges to those facing Russia in this area, while also looking at some countries that faced different problems but achieved interesting results.